PENGARUH PENYULUHAN MEDIA DENTAL STORY STICKER TERHADAP TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA SISWA SDN 22 BANDA ACEH - Keumala, Cut Ratna; Mardelita, Sisca; Safriani, Fahira (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2024)
The background of this study is that dental health counseling is often carried out, but the prevalence of dental caries in school-age children in Indonesia is still relatively high, exceeding the national target, namely DMFT <1. The success of school children's dental health counseling efforts cannot be separated from educational methods and the importance of the role of the media because it can support the learning process and can help understand the material. Through media, the message conveyed can be more interesting and easy to understand. The purpose of this study is to determine the effect of counseling using dental story sticker media on the level of knowledge of dental and oral health in grade I students of SD Negeri 22 Banda Aceh. This research methodology uses the Quasi-Experimental method with one group pretest-postest design. Determination of samples in this study using a saturated sample technique totaling 30 students. This research was carried out at SDN 22 Banda Aceh. The results showed that the average knowledge score of students before being given counseling using dental story stickers was 7.53 then increased to 12.17 after being given counseling using dental story stickers. based on paired t-test P=0.001 (p<0.05) so that there is an influence of dental and oral health counseling on dental and oral health knowledge using dental story stickers. The conclusion of the research results that there was a significant increase in knowledge of dental and oral health after counseling with dental story stickers. Advice Expected to students with dental health counseling to be applied in everyday life.